Efficiency of Tourism Operators’ and Tourism Agents’ Activities in the Market of Tourist Services of Ukraine - SAIENKO, Volodymyr; MEZENTSEVA, Inna; TOLCHIEVA, Hanna; SALKOVA, Iryna (Journal of Environmental Management and Tourism; Vol 11 No 8 (2020): JEMT Volume XI Issue 8(48) Winter 2020, 2021)
The article examines the effectiveness of tour operators and agents in the tourist services in Ukraine market based on the vouchers cost dependence  on  their sales volume to the population and the number of tourists served. The necessity to use such methods as correlation-regression analysis and adjusted least squares to evaluate the efficiency of these legal entities in the tourist services market is substantiated. The method of analysis of the operating environment has been used in the study of the positions of the regions of Ukraine where legal entities operate in the market of tourist services, which allowed by the number of tourist vouchers and tourists served to determine the directions of development of legal entities that allowed in its turn travel agents and tour operators to attract tourists and sell tourist vouchers to the population. It is revealed the direction of the modern market of tourist services development and according to it the effective development direction of the market of tourist services of Ukraine owing to activity of travel agents. The necessity of maximum coincidence of these directions is proved, while for travel agents in the regions of Ukraine there is no such coincidence. It is proposed to change the positions of the regions where these entities operate in an effective direction of the operating environment by reducing the cost of vouchers and increase tourism activity, as the study identified a number of areas where tourists pay higher vouchers cost than the national average. As the result of the environment of tour operators operation analysis in the regions of Ukraine, a special position in the Kharkiv region has been revealed, as one that allows to assess the effectiveness of these entities in all other regions of the country. A much larger organization in the tourist services market of tour operators is proved in comparison with travel agents, as the positions in the respective regions are currently in the direction of effective development with the exception of Ternopil, Khmelnytsky and Chernivtsi regions. Conclusions are made on the need to develop all business entities in the market of travel services, in particular to provide benefits from the travel agents activities.